1989
DOI: 10.3354/meps057237
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of nitrogen and carbon cycling in the northern Bering Shelf sediment. I. The significance of urea turnover in the mineralization of NH4+

Abstract: The impact of macrofauna on nitrogen and carbon mineralization was investigated in sediment of the shallow water Bering Sea Shelf. The main effort was focused on the probable role of macrofauna in the production of urea and the significance of urea turnover in the production of NH,+ Macrofaunal biomass was regulated by the quality and quantity of organic nitrogen available for degradation. This was illustrated by a low macrofaunal biomass in the sediment underlying the low productive Alaska Coastal water and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
77
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 25 publications
9
77
1
Order By: Relevance
“…Lomstein et al 1998). The same variability has been found in deeper estuaries, where in some cases DON was an important component of the TDN efflux (Lomstein et al 1989;Blackburn et al 1996) and in others it was small or insig- Comparison between light and dark (A) sediment fluxes and (B) macroalgal uptake/release of dissolved nitrogen. Error bars ϭ SE; n ϭ 72 each for light and dark for all measurements except amino acids, where n ϭ 60.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Lomstein et al 1998). The same variability has been found in deeper estuaries, where in some cases DON was an important component of the TDN efflux (Lomstein et al 1989;Blackburn et al 1996) and in others it was small or insig- Comparison between light and dark (A) sediment fluxes and (B) macroalgal uptake/release of dissolved nitrogen. Error bars ϭ SE; n ϭ 72 each for light and dark for all measurements except amino acids, where n ϭ 60.…”
Section: Discussionmentioning
confidence: 75%
“…Measurements of bulk DON, however, mask the dynamics of individual compounds, which vary widely in molecular weight and bioavailability (Burdige and Zheng 1998). For example, bioavailable compounds such as amino acids and urea may make up a significant portion of the DON pool and contribute to the benthic flux of DON (Boucher and Boucher-Rodoni 1988;Lomstein et al 1989;Burdige and Zheng 1998). In addition, these small, labile organic compounds may represent an important source of N for both heterotrophic and autotrophic microorganisms, as well as for benthic plants (Jorgensen 1982;Admiraal et al 1984;Lomstein et al 1989;Keil and Kirchman 1993;Nilsson and Sundback 1996;Rondell et al 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial reef structures enhance settlement of organic matter in the seabed with the biological and chemical degradation of dead plants and animals leading to benthic remineralization (Ambrose & Anderson, 1990;Lomstein et al, 1989;Rizzo, 1990 reported in a study on a benthic-pelagic coupling system, indicating that fresh organic input result in benthic activity enhancement (Gutiérrez et al, 2000). As animal metabolic activities and decomposition processes may be transforming larges quantities of particulate nitrogen into dissolved-reduced forms (Dame et al, 1986), the extremely low levels of organic nitrogen found in the seabed beneath the reef may be due to rapid turned over of nitrogen..…”
Section: Discussionmentioning
confidence: 98%
“…We used Nutricote® N (70 d, 40-0-0 N:P:K), a controlled release coated urea fertiliser containing no phosphorus, potassium or trace elements. A nitrogen-only fertiliser was used since it is typically the limiting nutrient in these systems, and urea quickly hydrolyses to ammonium (NH 4 + ) (Lomstein et al, 1989), the most common form of nitrogen in New Zealand estuaries (Tay et al, 2013). Fertiliser was applied to each plot in a series of 20 evenly spaced 3 cm diameter 15 cm deep holes made in the sediment using a hand held corer.…”
Section: Experiments Setupmentioning
confidence: 99%